2016
DOI: 10.1785/0220150255
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Cascadia G‐FAST Geodetic Earthquake Early Warning System for the Nisqually, Washington, Earthquake

Abstract: A prototype earthquake early warning (EEW) system is currently in development in the Pacific Northwest. We have taken a two-stage approach to EEW: (1) detection and initial characterization using strong-motion data with the Earthquake Alarm Systems (ElarmS) seismic early warning package and (2) the triggering of geodetic modeling modules using Global Navigation Satellite Systems data that help provide robust estimates of large-magnitude earthquakes. In this article we demonstrate the performance of the latter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
99
0
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 35 publications
1
99
0
4
Order By: Relevance
“…We must assess how well a particular method is able to capture these effects to improve ground-motion predictions. Additionally, although the current ShakeAlert system only includes pointsource-based alert methods, there are several methods under development that will predict additional source parameters, such as finite-fault length (e.g., Allen and Ziv, 2011;Böse et al, 2012) or slip distribution (Grapenthin et al, 2014;Minson et al, 2014;Crowell et al, 2016), as well as methods that predict ground motion directly from observed ground motion without requiring source information (e.g., Hoshiba, 2013;Hoshiba and Aoki, 2015;Kodera et al, 2016). The point-source-only assessment tools described in the Point-Source Assessment section are insufficient for determining the performance of these new methods.…”
Section: Ground-shaking Intensity Predictionsmentioning
confidence: 99%
“…We must assess how well a particular method is able to capture these effects to improve ground-motion predictions. Additionally, although the current ShakeAlert system only includes pointsource-based alert methods, there are several methods under development that will predict additional source parameters, such as finite-fault length (e.g., Allen and Ziv, 2011;Böse et al, 2012) or slip distribution (Grapenthin et al, 2014;Minson et al, 2014;Crowell et al, 2016), as well as methods that predict ground motion directly from observed ground motion without requiring source information (e.g., Hoshiba, 2013;Hoshiba and Aoki, 2015;Kodera et al, 2016). The point-source-only assessment tools described in the Point-Source Assessment section are insufficient for determining the performance of these new methods.…”
Section: Ground-shaking Intensity Predictionsmentioning
confidence: 99%
“…Hundreds of real-time high-precision GNSS stations are now becoming available on the West Coast (Mencin et al, 2013), and these may contribute to the ShakeAlert system's ability to characterize large events, especially by modeling the location and extent of the fault rupture (Allen and Ziv, 2011;Böse et al, 2013). Recently, scientists have developed algorithms that use real-time GNSS data to estimate magnitudes for large earthquakes (M > 6:0) and solve for the distribution of fault slip (Grapenthin et al, 2014;Minson et al, 2014;Crowell et al, 2016). Mapping the evolving rupture is important for calculating the magnitude of large events and for correctly estimating the intensity that will result across a region.…”
Section: Sensor Networkmentioning
confidence: 99%
“…A possible technology for real-time computation of a finite-fault estimate is established using real-time Global Navigation Satellite System (GNSS) positioning technology, which provides real-time three-dimensional ground displacements (e.g., Blewitt et al 2009;Ohta et al 2012Ohta et al , 2015Crowell et al 2012Crowell et al , 2016 Open Access *Correspondence: kawamoto-s96tf@mlit.go.jp 1 Geodetic Observation Center, Geospatial Information Authority of Japan, 1 Kitasato, Tsukuba, Japan Full list of author information is available at the end of the article Grapenthin et al 2014;Kawamoto et al 2015;. The Geospatial Information Authority of Japan (GSI) has operated a continuous real-time GNSS network, named GEONET, which consists of more than 1300 stations.…”
Section: Introductionmentioning
confidence: 99%